PENGEMBANGAN DAN PENGELOLAAN EBONI DALAM SISTEM DAERAH PENYANGGA - Bismarck, M. (Research Center for Biology-Indonesian Institute of Sciences, 2002)
The increasing value of ebony (Diospyros celebica Bakh.) recently, causes extensive exploration of the species, and as the consequency the natural population of this species become endangered.Conservation of ebony depends on the management of the Nature Conservation areas or the National Parks in Sulawesi.Conserving the gene pool and management of the surrounding area i.e.the buffer zone is important for the species diversity and the social economic aspect of the local community.The buffer zone has three different functions, as greenbelt zone, interaction zone and cultivation zone.These zones are managed in an integrated system where the progress of the region is responsible on the conservation and community development is implemented. The progress of the ebony forest plantation and agriculture zone of the buffer zone area develops into a mixed plantation forest of an agroforestry system in a community forest management.